The potential impact of changes in income distribution on food demand and human nutrition - Pinstrup-Andersen, Per; Caicedo, Elizabeth (Wiley, 1978)
A procedure is developed to estimate nutritional and food demand implications of changing consumer income distribution. Findings from an empirical application to the population of Cali, Colombia, suggest that changes in income distribution can effectively improve human nutrition, even in the absence of food supply expansions. These same changes also have a large impact on the demand for individual food commodities. In societies where significant changes occur in income distribution, commodity demand projections preferably should be based on individual stratum rather than on average estimates of price and income elasticities.